2018
DOI: 10.3390/app8122371
|View full text |Cite
|
Sign up to set email alerts
|

Combination of High-Resolution Optical Coherence Tomography and Raman Spectroscopy for Improved Staging and Grading in Bladder Cancer

Abstract: We present a combination of optical coherence tomography (OCT) and Raman spectroscopy (RS) for improved diagnosis and discrimination of different stages and grades of bladder cancer ex vivo by linking the complementary information provided by these two techniques. Bladder samples were obtained from biopsies dissected via transurethral resection of the bladder tumor (TURBT). As OCT provides structural information rapidly, it was used as a red-flag technology to scan the bladder wall for suspicious lesions with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
(56 reference statements)
1
27
0
Order By: Relevance
“…Furthermore, the sensitivity of detecting high grade lesions with RS was 99%, whereas the specificity was 87%, indicating correct detection of low grade lesions. 55 To use these techniques in vivo in the clinics, they need to be integrated into rigid or flexible cystoscopes to allow in situ assessment of the bladder wall. As a first step in this direction, we report on the development of a combined OCT-Raman system for stage and grade examination of bladder biopsies, based on fiber-optical probes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sensitivity of detecting high grade lesions with RS was 99%, whereas the specificity was 87%, indicating correct detection of low grade lesions. 55 To use these techniques in vivo in the clinics, they need to be integrated into rigid or flexible cystoscopes to allow in situ assessment of the bladder wall. As a first step in this direction, we report on the development of a combined OCT-Raman system for stage and grade examination of bladder biopsies, based on fiber-optical probes.…”
Section: Introductionmentioning
confidence: 99%
“…The first principal components (PCs) of a spectral data set usually represent its most relevant spectral features, which eventually can be associated to the presence of specific molecules. In particular, methods based on mixing the information provided by different PCs have already been applied to the classification of UC Raman spectra . Hence, for each spectroscopic technique, we used a classification method based on different linear combinations of the first six PCs.…”
Section: Methodsmentioning
confidence: 99%
“…Raman scattering allows to analyse the chemical composition of biological systems by probing the vibrational energy levels of molecules, hence providing highly specific information on tissue molecular composition. In particular, this technique has been used for detecting bladder cancer and for discriminating different tumour stages and grades . Finally, reflectance spectroscopy is a well‐established technology for measuring both colour and intensity of light reflected from tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It relies on the effect of inelastic scattering of photons, stimulating molecular vibrations providing specific information on the chemical composition and molecular structure, and is an emerging technique in life sciences owing to its unique capability of generating spectroscopic fingerprints of cells and tissues in a nondestructive and label-free approach. It has been demonstrated that the combination OCT/RS on cancerous tissue can increase diagnostic sensitivity, specificity and accuracy compared to a single modality [57]. Two-photon excited fluorescence (TPEF) microscopy can be used to visualize endogenous fluorophores such as NADH and FAD giving information about redox states.…”
Section: Preclinical Hybrid Imagingmentioning
confidence: 99%
“…Advanced PHI includes R&D setups and pipelines that showcase combinations of in-vivo OI, OCT/PAI, US, MRI, CT, or PET [8,76]. Examples as outlined in section Preclinical Hybrid Imaging include label-free imaging using OCT and RS [57], or the combination of MRI and OI [77].…”
Section: Novel CMI Pipelinesmentioning
confidence: 99%